Arginase inhibition improves endothelial function in patients with familial hypercholesterolaemia irrespective of their cholesterol levels. (28th December 2015) - Kovamees, O.; Shemyakin, A.; Eriksson, M.; Angelin, B.; Pernow, J.
Abstract: Background: Elevated LDL cholesterol is an important risk factor for atherosclerosis. Endothelial dysfunction, an early event in the development of atherosclerosis, is characterized by a reduction in nitric oxide (NO) bioavailability. Arginase has emerged as a key regulator of endothelial function through competition with NO synthase for the common substratel ‐arginine. Arginase in endothelial cells is activated by oxidized LDL. The study aim was to investigate the importance of arginase for endothelial dysfunction in patients with familial hypercholesterolaemia (FH). Methods and results: Endothelial function was evaluated in 12 patients with heterozygous FH and 12 age‐matched healthy normocholesterolaemic subjects using forearm venous occlusion plethysmography. The evaluations in FH patients occurred when they were on lipid‐lowering therapy and 4 weeks after withdrawal of treatment. Endothelium‐dependent vasodilatation (EDV) was assessed by intrabrachial artery infusion of serotonin, and endothelium‐independent dilatation was assessed by infusion of nitroprusside before and after 120 min administration of the arginase inhibitor N ω ‐hydroxy‐nor‐l ‐arginine (nor‐NOHA; 0.1 mg min −1 ). In FH patients LDL cholesterol increased from 4.3 ± 0.9 mmol L −1 at baseline to 7.6 ± 1.9 mmol L −1 at follow‐up ( P < 0.001). Arginase inhibition enhanced EDV in FH patients by a similar degree independent of lipid‐lowering therapy. The improvement in EDV by arginase inhibition was significantly greater in FH patients than in the control group. Conclusion: Arginase inhibition results in greater improvement in endothelial function in patients with FH compared to healthy controls irrespective of their cholesterol levels. Arginase may be a promising therapeutic target for improving endothelial function in patients with hypercholesterolaemia.